Guideline for promoting Public Participation in Community development of Huahin Municipality, Prachuap Khiri Khan province - Krudminburee, julamas (Journal of MCU Phetchaburi Review, 2025)
This Mixed Method Research aimed to study (1)level of public participation, (2)the difference between personal factors and public participation, (3)causal relationship between factors affecting public participation and public participation, and (4)guideline for promoting public participation in community development. The sample group used in the research was representative of people in Hua Hin Municipality, totaling 400people, living in Hua Hin Municipality, and the target group of key informants consisted of 15 people. Data were treated and analyzed by using descriptive and Inferential Statistics methods, which were percentage, mean, standard deviation, One-way analysis of variance, and Multiple Regression Analysis. Research results : (1) Public participation in community development in terms of decision-making, operations, receiving benefits, and monitoring and evaluation, overall, participation was at a high level. (2) Individual characteristics with different levels of education had a statistically significant difference in public participation in community development at a .05 level, and in terms of occupation, at a statistically significant level at a .01 level. (3) Factors in public participation in terms of knowledge and understanding, community commitment, community leadership, communication, and people’s way of life had a cause-and-effect relationship with public participation in community development at a statistically significant level at a .001 level. (4) Guidelines for developing public participation in community development found that people should be encouraged to participate in training, projects, and various activities organized by Hua Hin Municipality. Projects or activities that people are interested in should be organized. People should be encouraged to be on the monitoring and evaluation committees in various groups in a proportion that can make decisions. Public relations on the results of operations should be provided for people to follow up and evaluate through various channels. Keywords : Public Participation, Community Development